Use of EPR Spectra Peculiarities of Transition Metal Ions When Studying Salt Concentrating Depending on Freezing Conditions - Nardid, Oleg A. (Problems of Cryobiology and Cryomedicine, 2014)
The EPR spectra of frozen salt solutions of paramagnetic cations were studied. The spectra structure and shape were demonstrated to be dependent on regimen and composition of freezing medium. The obtained experimental EPR spectra are theoretically described by spin Hamiltonian containing axially symmetric term of fine structure with manifestation of forbidden Î”m = Â±1 transitions. There was proposed to use EPR approaches in designing low temperature technologies for biological object preservation to analyze freezing regimens and possible cryoprotectants to forecast the minimization of cryoinjury effects with high salt concentrations during freezing. Probl Cryobiol Cryomed 2014; 24(3):212-221.